ENERGY-EFFICIENT MANAGEMENT OF SMALL-SCALE SETTLEMENTS, AN ASSESSMENT FOR LAPSEKI CITY - Sinmaz, Serkan; Yenen, Zekiye (YILDIZ TECHNICAL UNIV, 2015)
Since the last quarter of the 20th century, demand for energy increases in the world and energy production and consumption processes bring ecological problems in parallel with emerging technology and urbanization. For this reason, various initiatives, plans and implementations emphasize theimportance of less energy consumption in cities from the 90s on. For remodeling of the cities of the near future according to this strategy, especially in the context of urban transformation, physical settlement plans should be dealt with according to the energy efficiency concept. In this context, the planning process to be developed reveals a significant opportunity for the healthy development of small-scale cities which did not go beyond the geographical and social boundaries and is outnumbered compared to large-scale cities having growth potential in parallel with emerging technology and urbanization. This study that is at the point of addressing on physical settlement plan construction process describes energy-efficient evaluation model and presents an experimental application in Lapseki which is a small-scale settlement in the Dardanelles.
Keywords: Energy efficient settlement; small scale settlement.; Engineering